“The Eyes of the Lord” - Oppenheim, A. Leo
a rather specific social practice and its institutionalized modus operandi. Informers, accusers, internal spies, censors, secret agents and their like form. . . an effective and often unobtrusive web, that with constant vigilance and demonic effectiveness directs, controls and coerces the individual in his social setting. . . transferred to a supernatural level . . . they appear either as evil demons, as the swift messengers and servants or the “Eyes of the Lord”.